1983
DOI: 10.1161/01.hyp.5.5.642
|View full text |Cite
|
Sign up to set email alerts
|

Sodium and potassium ion transport accelerations in erythrocytes of DOC, DOC-salt, two-kidney, one clip, and spontaneously hypertensive rats. Role of hypokalemia and cell volume.

Abstract: SUMMARY Sodium (Na + ) and potassium (K + ) transport by the furosemide-sensitive Na + -K + transport system, the Na + -K + pump, and the cation leak(s) were studied in erythrocytes from DOCwater, DOC-salt, two-kidney, one clip (Sprague-Dawley), and spontaneously hypertensive rats (Wistar-Kyoto). Rubidium (Rb + ) was used as a tracer for K + . After 4 weeks of DOC-salt hypertension, inward K + (Rb + ) transport by the furosemide-sensitive system was increased threefold, and the inward Na + leak and the red cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1984
1984
1992
1992

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…It thus differs from the regulatory volume decrease and the response towards catecholamines found in bird erythrocytes [29,32,34] and from the "uncoupling" of Na + from K + movements seen in swollen human erythrocytes [1]. Finally, furosemide-sensitive K + transport is not [11] or only slightly [1] volume dependent in human erythrocytes, in contrast to the system found in bird [25,29,32,40] and rat erythrocytes [12,13].…”
Section: Driving Forcesmentioning
confidence: 94%
See 1 more Smart Citation
“…It thus differs from the regulatory volume decrease and the response towards catecholamines found in bird erythrocytes [29,32,34] and from the "uncoupling" of Na + from K + movements seen in swollen human erythrocytes [1]. Finally, furosemide-sensitive K + transport is not [11] or only slightly [1] volume dependent in human erythrocytes, in contrast to the system found in bird [25,29,32,40] and rat erythrocytes [12,13].…”
Section: Driving Forcesmentioning
confidence: 94%
“…9 are the calculated working points of the furosemide-sensitive transport system in erythrocytes of normal (A) and K+-depleted rats (B) [12]. The furosemidesensitive transport system of rat erythrocytes is similar to that of human erythrocytes, except that the maximum transport rates in the rat increase more than 10-fold upon cell shrinkage [12,13], a phenomenon not seen with human erythrocytes [11]. Due to the low stationary Na + concentration in normal rat erythrocytes the furosemide-sensitive transport system should work in the inward direction.…”
Section: Role Of the Furosemide-sensitive Transport System In Vivomentioning
confidence: 99%
“…Noting that deoxycorticosterone enanthate treatment of rats without dietary sodium loading caused a significant increase in sodium but not in rubidium leak, the authors concluded that leak pathways for monovalent cations may differ. 22 A more thorough examination of the changes in the kinetics of lithium transport induced by DOCA treatment in pig red cells and an examination of the relation of changes detected in red cells to cation metabolism in vascular tissues will be necessary to relate our observations to those in other species.…”
Section: Discussionmentioning
confidence: 98%
“…18 " 21 However, changes in red blood cell cation transports in response to mineralocorticoid treatment have not been as extensively studied. Duhm et al 22 described enhanced sodium and rubidium diffusional leaks in deoxycorticosterone enanthate NaCl hypertensive rat erythrocytes but did not assess lithium movements. Noting that deoxycorticosterone enanthate treatment of rats without dietary sodium loading caused a significant increase in sodium but not in rubidium leak, the authors concluded that leak pathways for monovalent cations may differ.…”
Section: Discussionmentioning
confidence: 99%
“…Alteration in the activity of Na+,K"-ATPase, a membrane enzyme primarily responsible for Na* and K* transport in most animal cells has been well investigated as one of the causes for changes in Na* and Ki distribution. In spontaneously hypertensive rats (SHR), an enhanced Na*,I(*-ATPase activity has been reported (7,8,10,22,28). On the other hand, other groups have reported similar (1) or reduced (12,13,18,25) levels of Na*,l(*-ATPase activity as compared with the normotensive control, Wistar Kyoto rats (WKY).…”
mentioning
confidence: 99%